Human interaction in the NICU and its association with outcomes on the Brief Infant-Toddler Social and Emotional Assessment (BITSEA). (December 2018) - Gonya, J.; Feldman, K.; Brown, K.; Stein, M.; Keim, S.; Boone, K.; Rumpf, W.; Ray, W.; Chawla, N.; Butter, E.
Abstract: Background: Extremely preterm infants represent one of the highest risk categories for impairments in social competence. Few studies have explored the impact of the neonatal intensive care unit (NICU) environment on social development. However, none have specifically analyzed the effects of the care structure the infant receives during hospitalization on later social competence indicators. Objective: To identify associations between the care structures received by extremely preterm infants in the NICU and scores on the Brief Infant-Toddler Social and Emotional Assessment (BITSEA) post-discharge. Participants: 50 extremely preterm infants (mean gestational age: 25 weeks during hospitalization; mean chronological age during follow-up assessment: 2 years, 4 months). Methods: A secondary analysis of BITSEA data was performed exploring its relation to care structure data we extracted from electronic medical records (i.e., how much time infants were engaged in human interaction during their first thirty days of hospitalization and what types of interaction they were exposed to). Results: Extremely preterm infants spend a considerable amount of time alone during hospitalization (80%) with nursing care comprising the majority of human interaction. Infants who experienced greater human interaction scored significantly higher on the Social Competence (p = 0.01) and lower on the Dysregulation (p = 0.03) BITSEA subscales. Conclusion: Human interaction and isolation in the NICU is associated with social competence and dysregulation outcomes in extremely preterm infants. Further research is needed to understand how various NICU care structures including centralized nursing teams, parental skin-to-skin care, and early therapy may synergistically play a positive role in developing social competence. Highlights: Extremely preterm infants spend an inordinate amount of time alone during their first thirty days in the NICU. The majority of human interaction encountered by extremely preterm infants is comprised of nursing care. Social competence, dysregulation, and ASD scores on the BITSEA are associated with nursing care structure in the NICU. Future studies should explore how to increase meaningful human interactions with extremely preterm infants in the NICU.